Validation of the Psychometric Properties of Acceptance and Action Questionnaire-II in Clinical and Nonclinical Groups of Portuguese Population - Costa, Joana (2018)
This study explores the factor structure of the Acceptance and Action Questionnaire (AAQ-II) in both clinical and general normative groups. It also examines the factorial invariance of a one-factor proposed model in both groups. Data was collected from the overall database of a Portuguese Cognitive and Behavioral Research Center (N= 687, 425 females; mean age= 36 years; SD= 11.33). Conrmatory Factor Analysis supported a one-factor structure with good internal consistencies and construct related validity. The one-factor solution was also supported with a second independent data set, which showed a congural, strict measurement and structural invariance of the one-factor solution proposed. Multigroup Conrmatory Factorial Analysis showed the congural invariance, weak measurement invariance and also structural invariance of the one-factor model of Acceptance and Action Questionnaire II across both groups under study. The one-factor model have both similar meanings and the same structure, but the measurement model in clinical and nonclinical groups was not the same. Toxic inuences of experiencial avoidance as a core mechanism in the development and maintenance of several clinical disorders, may explain why the AAQ-II does not operate equivalently across clinical and nonclinical groups. Key words: experiential avoidance, one-factor model, factorial invariance, clinical and nonclinical groups.